MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANIMASI UNTUK PEMBELAJARAN MAKHRAJ HURUF HIJAIYAH - Fuadi Alhusaini; Nur Afif; Faisal Akib (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
The use of multimedia technology as a learning medium is an alternative for learning that is more interesting and easy to understand, as well as in the process of learning to read the Koran with correct recitation, a Qary must pay attention to how to pronounce hijaiiyah letters correctly according to his reading makhraj. This research aims to help implement the pronunciation of the hijaiyyah letters properly and according to the rules by using the Hijaiyyah Letter Makhraj learning media which can help readers to avoid speech errors that cause changes in the meaning of the sentences spoken when reading the Koran. This type of research is quantitative research. The quantitative research carried out is an experimental research method by conducting experiments on control variables (input) to analyze the resulting output. The resulting output will be compared with the output without controlling the variables. The result of this research is a learning media for hijaiyyah makhraj letters by displaying the movements of the mouth and tongue. Learning medium could be used by Muslims in order to know how to distinguish the pronunciation of hijaiyyah letters so that they avoid errors in reading that can result in changes in the meaning of the sentences they pronounce and provide an explanation of the differences between letters and their sounds, namely by showing an animation of mouth movements in 3D objects as well as the sound of their pronunciation and explanations of letters